Longitudinal Effects of Activity-Based Flexible Office Design on Teamwork - Wohlers, Christina; Hertel, Guido (Frontiers in Psychology, 2018)
This three-wave longitudinal interview study (time lag: 12 and 18 months) investigates the impact of working in an activity-based flexible office (A-FO) on processes within and across teams (i.e., communication, trust, cohesion and collaboration) and team management. Based on a new theoretical framework on benefits and risks of A-FOs (A-FO-M; Wohlers & Hertel, 2017), we conducted interviews with 25 employees of an in-house training institute who recently switched from single cell or shared offices to an A-FO. The A-FO consisted of a main open-layout environment without assigned workstations and provided additional working zones appropriate for specific work activities. According to the A-FO-M, A-FO features are expected to alter visibility and proximity of employees as compared to office environments with assigned workstations. Altered visibility and proximity, in turn, should be related to team processes, such as communication. The interview material was analyzed using qualitative content analysis. This textual analysis procedure revealed that the interviewees reported that inter-team collaboration improved while working in the A-FO. Reasons that were mentioned for this positive effect were more contact, communication, collaboration possibilities (joint project work) and trusting relationships. However, interviewees also reported negative effects, such as that teamwork suffered due to fewer communication and cooperation. Along with that, especially ensuring team cohesion and communication among team partners were the most often mentioned challenges for management since team members were spatially dispersed within the office building. Theoretical and practical implications, such as assigning additional team areas to support teamwork, as well as recommendations for future research are discussed.